Pengenalan Aplikasi Si Apik Bagi Umkm Warung Manisan Pak Agung - Hidayah, Nenden Restu; Susena, Karona Cahya; Rahayu, Hesti Riski; Astiana, Cemas (Jurnal Dehasen Untuk Negeri, 2025)
Si Apik application is a digital innovation designed to facilitate the management of micro, small, and medium enterprises (MSMEs). This journal discusses the implementation and impact of using the Si Apik application at Warung Manisan Pak Agung, an MSME engaged in the sale of traditional sweets. This study uses qualitative methods, involving in-depth interviews with the owner and customers, as well as direct observation of the store's operations. The results of the study show that the use of the Si Apik application not only increases operational efficiency, such as stock management and transaction recording, but also has a positive impact on customer satisfaction through faster and more accurate services. These findings indicate the significant potential of the Si Apik application in supporting the digital transformation of other MSMEs in Indonesia.